KEBIJAKAN KRIMINAL TERHADAP PENCEGAHAN TINDAK PIDANA PERDAGANGAN ORANG - Elsa Rina Maya Toule (MIZAN, Jurnal Ilmu Hukum, 2020)
Human trafficking as a form of adult crime has been very widespread. Carried out by an organized network, crossing national borders using various methods to sophisticated technology. By involving cross-country organizations and by using sophisticated technology, trafficking in persons is a crime that requires systematic and comprehensive treatment. Trafficking in persons is not only a matter of a country, but rather a cross-country or international problem. The purpose of this study was to determine the criminal policy against the prevention of criminal acts of civilization, the method of writing is normative juridical. The results of the study show that strategies and policies for handling it cannot be expected by only using criminal law facilities, but also non-criminal means. Legal policies are carried out on preventing the crime of trafficking in persons, particularly criminal law which is oriented to the protection and guarantees of human rights law. The aim is to protect the human rights of every citizen, which is not only oriented to the giving of punishments and non-punishments to perpetrators, but is prioritized to protect witnesses and victims, so prevention efforts must be optimal, synergistic, integrated and sustainable, coordinated, involving all components in society. Indonesia is a country that is vulnerable to the crime of trafficking in persons, because the archipelago, a large population, with an unequal level of economic life and can be accessed through many entry points, makes Indonesia a country of origin for victims. The mere presence of a law against trafficking in persons does not benefit. This law must be supported by a variety of other policies, both in the form of other laws and regulations, as well as other strategic policies which are internal policies of related institutions and regional regulations.